Developing a cumulative anatomic scoring system for military perineal and pelvic blast injuries. (1st March 2013) - Mossadegh, Somayyeh; Midwinter, M; Parker, P
Abstract : Background: Improvised explosive device (IED) yields in Afghanistan have increased resulting in more proximal injuries. The injury severity score (ISS) is an anatomic aggregate score of the three most severely injured anatomical areas but does not accurately predict severity in IED related pelvi-perineal trauma patients. A scoring system based on abbreviated injury score (AIS) was developed to reflect the severity of these injuries in order to better understand risk factors, develop a tool for future audit and improve performance. Method: Using standard AIS descriptors, injury scales were constructed for the pelvis (1, minor to 6, maximal). The perineum was divided into anterior and posterior zones as relevant to injury patterns and blast direction with each soft tissue structure being allocated a score from its own severity scale. A cumulative score, from 1 to 36 for soft tissue, or a maximum of 42 if a pelvic fracture was involved, was created for all structures injured in the anterior and posterior zones. Results: Using this new scoring system, 77% of patients survived with a pelvi-perineal trauma score (PPTS) below 5. There was a significant increase in mortality, number of pelvic fractures and amputations with increase in score when comparing the first group (score 1–5) to the second group (score 6–10). For scores between 6 and 16 survival was 42% and 22% for scores between 17 and 21. In our cohort of 62 survivors, 1 patient with an IED related pelvi-perineal injury had a 'theoretically un-survivable' maximal ISS of 75 and survived, whereas there were no survivors with a PPTS greater than 22 but this group had no-one with an ISS of 75 suggesting ISS is not an accurate reflection of the true severity of pelvi-perineal blast injury. Conclusions: This scoring system is the initial part of a more complex logistic regression model that will contribute towards a unique trauma scoring system to aid surgical teams in predicting fluid requirements and operative timelines. In austere environments, it may also help to prevent futile resuscitations. Better correlation between measurement of severity and outcome would aid performance improvement monitoring. In the longer term it will also allow benchmarking of current survival rates and comparisons in the future.